Sustainable keratoplasty models using agri-food waste: a hypothesis for transforming biowaste into biomaterials for tissue engineering research - Corridon, Peter R.; Mobin, Ayman; Hashem, Zayd; Paunovic, Jovana; Valjarevic, Svetlana; Pantic, Igor V. (Frontiers in Sustainable Food Systems, 2025)
With a growing global population, ways to counterbalance the demand for meat products with effective food security and waste management demand innovative and scalable solutions. Concurrently, the alarming incidence of end-stage organ failure, limited availability of transplantable organs, and directives to reduce reliance on animal testing underscore the need for clinically viable and sustainable alternatives. Our approach introduces a hypothesis-driven, renewable tissue engineering strategy that creates low-cost keratoplasty models derived entirely from agri-food waste. Specifically, we hypothesize that abundant meat by-products, such as eyes and bladders, provide practically unlimited and readily available supplies of corneal tissues and urine-derived stem cells (USCs) that can be repurposed into cost-effective, clinically relevant solutions. Traditional approaches often rely on cadaveric tissues, invasive cell sourcing, or expensive commercial stem cell lines, which require complex and resource-intensive processes, including high-end bioreactor systems and manufacturing environments. These requirements often limit the widespread adoption and technological progress needed to increase the global supply of keratografts. Our proposed strategy leverages a combination of post-mortem corneal and bladder harvesting, which in turn facilitates tissue decellularization, non-invasive USC sourcing, stem cell differentiation, and compartment-specific recellularization approaches to help overcome barriers associated with traditional cell seeding and generate keratoplasty models derived entirely from this type of waste. Overall, our perspective suggests a way to devise a transformative and resource-efficient approach to tissue engineering, specifically geared toward improving keratoplasty outcomes while offering broader applications for the regeneration of other bodily tissues/organs and biotechnological innovation.